Neuropsychological study of anxiety. Depression and quality of life in patients with atrial fibrillation - Llaja Rojas, Victoria (2015)
The objective of this research is to describe and analyze the disorders of the psychic activity staff of patients with atrial fibrillation; and explain the commitment of its functional activity using the theoretical model of the personality sociobiologic (MOS) (Ortiz, 1994, 1995, 1997, 1997b, 1998, 1999, 2002). The sample shall be composed of all patients diagnosed by a medical specialist, which have presented an episode or more of atrial fibrillation, after having suffered anxiety and recurrent depression, which in previous studies it has been recorded that brings change in their quality of life (Chest,2007), and we would like to explain a posteriori the dysfunctional aspects that have been given in the affective processing- emotive, cognitive-productive and intellect-related symptoms were mental information of the aware of the individual.The non-probabilistic sampling is intentional, and will collect the data during the period January to October 2014. The design would be descriptive, observational, cross,and retrospective clinical trial according to the classification of Hernández, Fernandez & Baptista . (2010) The population of study should consist of all the income in the Service of Cardiology and Neurology (hospitalization and outpatient ERMH (hospitalization 11 A - B and outpatient-53) Should be administered the neuropsychological battery POC -2005 revised (Sarria, Llaja & Garcia, 2008),and specialized tests Personality Profile (SNP)and the Questionnaire AF-QOL (Atrial Fibrillation-Quality of Life) that is a specific questionnaire of 18 items, grouped in three dimensions, with Likert responses with five categories. For the analysis of the data will be used the SPSS, version 17, for the calculation of frequencies and percentages, and other parametric measures, which establish the description and explanation of the dysfunctional aspects in the three components of the system of the personality. It is also interpreted the findings through the SOP Model, which is demonstrating its validity in the clinical study of these comprehensive neuropsychological disorders, and tested some psychotherapeutic measures of preventive treatment if the case warrants it. It is arrived to the following conclusions: 1.- Relationship between indicators of mixed anxiety disorder - depression (F 41.2) and a negative evaluation of the components of quality of life in patients with atrial fibrillation (AF) as an associated factor. 2.- Also, we find that there is no predominant personality profile associated with Atrial Fibrillation as a predisposing factor, being more frequent the unyielding in our sample. 3.- There is a dysfunction of the priority component of the temperament in the system of Personality of the affected individuals with atrial fibrillation. 4.- The quality of life of patients with atrial fibrillation presents characteristic unhealthy habits, in the psychological Domain. 5.- In addition it has validated a scale for the Evaluation of the psychological factor subjective, applied to clinical population, with indicators psychological, sexual, and attitudinal; thus the questionnaire AF-QoL has shown its usefulness as an effective tool in clinical practice, with good index of feasibility, validity, and reliability.